Physical Activity Adoption to Adherence, Lapse, and Dropout: A Self-Determination Theory Perspective - Kinnafick, F.; Thøgersen-Ntoumani, Cecilie; Duda, J. (Sage Publications, 2014)
Grounded in Self-Determination Theory, we aimed to explore and identify key motivational processes involved in the transition from a physically inactive to an active lifestyle, and the processes involved in lapse and dropout behavior within a walking program. We implemented a qualitative, longitudinal case study method, using semistructured interviews and theoretical thematic analyses. Fifteen women were interviewed over 10 months and three profiles were generated: (a) nonadherence, (b) lapse/readoption of physical activity, and (c) adherence. Internalization of walking behavior was key to adherence. Satisfaction of the needs for competence and relatedness were central for participation during exercise at the adoption stages, and autonomy was particularly pertinent in facilitating adherence. Those who lapsed and restarted physical activity experienced feelings of autonomy at the point of readoption. Sources of support were driving forces in the adoption and adherence phases.